Immune-related gene SOX10 affects ferroptosis in pancreatic cancer and facilitates tumor progression by targeting CMTM7-mediated Wnt/β-catenin signaling pathway - Guixing Jiang; Bicheng Wu; Kaikai Wang; Xiaofan Pu; Senhao Zhou; Xin Zhong; Xiaolong Liu; Suihan Wang; Tianyu Lin (European Journal of Medical Research)
Abstract Objectives SOX10 is crucially implicated in various cancer, yet the regulatory role in pancreatic cancer (PC) remains enigmatic. Underlying molecular mechanisms of SOX10 in PC were explored in our study. Methods Relationships between SOX10 and immune landscape were estimated using bioinformatic approaches. The expression of SOX10 and CMTM7 was analyzed using quantitative real-time polymerase chain reaction and western blot. To assess cell functions, cell counting kit-8, flow cytometry, scratch test, and Transwell assays were performed. Dual-luciferase assay was performed to confirm the target-binding relationship of SOX10 and CMTM7. After knocking down SOX10 using lentiviral transfection, SOX10 action on Wnt/β-catenin pathway and ferroptosis, as well as its anti-tumor activity in tumor-bearing mice were explored. Results SOX10 was significantly correlated with immune infiltrations, checkpoints, and characteristics in PC. Mechanically, SOX10 level was increased and CMTM7 was down-regulated in both PANC-1 cells and PC tissues. When SOX10 was downregulated or CMTM7 was overexpressed, it notably hindered the cells' activity, while also promoting cell apoptosis in vitro. Meanwhile, CMTM7 is regulated by SOX10 in the downstream, and its silencing significantly reversed the inhibition of sh-SOX10 on PANC-1 cells growth and Wnt/β-catenin pathway. Furthermore, overexpression of CMTM7 induced ferroptosis in PC by inhibiting the Wnt/β-catenin pathway. More interestingly, by targeting CMTM7-mediated Wnt/β-catenin signaling pathway, the knockdown of SOX10 was confirmed to induce ferroptosis in PC and suppress tumor progression in vivo. Conclusions SOX10 is deemed as an immune-related gene. Its knockdown induces ferroptosis in PC and suppresses tumor progression via CMTM7-mediated Wnt/β-catenin pathway.